2009
DOI: 10.1111/j.1742-4658.2009.07105.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of structural determinants for inhibition strength and specificity of wheat xylanase inhibitors TAXI‐IA and TAXI‐IIA

Abstract: Triticum aestivum xylanase inhibitor (TAXI)-type inhibitors are active against microbial xylanases from glycoside hydrolase family 11, but the inhibition strength and the specificity towards different xylanases differ between TAXI isoforms. Mutational and biochemical analyses of TAXI-I, TAXI-IIA and Bacillus subtilis xylanase A showed that inhibition strength and specificity depend on the identity of only a few key residues of inhibitor and xylanase [Fierens K et al. Crystallographic analysis of the structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…It may therefore be hypothesized that a subset of S. sclerotiorum critical secreted enzymes are engaged in an evolutionary arms race with plant pattern recognition receptors, driving opposing forces of natural selection S. sclerotiorum effector genes. Since plant inhibitors are known for many fungal cell wall degrading enzymes, it is also possible that an evolutionary arms race with plant inhibitors drives the evolution of some S. sclerotiorum effector candidates [53, 62, 63]. Remarkably, we also identified 14.4% of species-specific SPEP genes.…”
Section: Discussionmentioning
confidence: 72%
“…It may therefore be hypothesized that a subset of S. sclerotiorum critical secreted enzymes are engaged in an evolutionary arms race with plant pattern recognition receptors, driving opposing forces of natural selection S. sclerotiorum effector genes. Since plant inhibitors are known for many fungal cell wall degrading enzymes, it is also possible that an evolutionary arms race with plant inhibitors drives the evolution of some S. sclerotiorum effector candidates [53, 62, 63]. Remarkably, we also identified 14.4% of species-specific SPEP genes.…”
Section: Discussionmentioning
confidence: 72%
“…In contrast, Leu292 in IL‐1 of TAXI‐IA undergoes a hydrophobic interaction with Tyr10 of ANXY. The interactions mimic those in the enzyme–substrate complexes (PDB ID 1BCX and 2QZ2) [7,9]. In addition, His374 of TAXI‐IA interacts with Asp37 of ANXY.…”
Section: Resultsmentioning
confidence: 96%
“…The structure of TAXI‐IA in complex with Aspergillus niger xylanase (ANXY), a GH11 xylanase from Aspergillus niger , coupled with functional studies, has revealed that His374 of TAXI‐IA plays a significant role in the inhibition of ANXY, where His374 interacts with the catalytic Glu79 and Glu170 of ANXY [7,8]. Furthermore, it has been reported that the hydrophobic interaction of Leu292 of TAXI‐IA with Pro294 of TAXI‐IIB regulates the strength of inhibition and specificity for GH11 xylanases [9].…”
Section: Introductionmentioning
confidence: 99%
“…The flasks were then incubated in a rotary incubator at 200 rpm at 37°C. Various parameters, such as pH (4)(5)(6)(7)(8), temperature (16-42°C), effect of time of induction (1-7 h), and effect of different IPTG concentrations (0.1 to 0.6 mM) were studied for the optimum production of the xylanase enzyme.…”
Section: Shake Flask Studiesmentioning
confidence: 99%
“…Two main families of glycosyl hydrolases, family 10 and family 11, represent the endoxylanases, categorized on the basis of their sequence similarities and hydrophobic cluster analysis [8]. These two families of endoxylanases are further differentiated on the bases of their molecular weights, e.g., family 10 comprises endoxylanases of larger molecular weights higher than 40 kDa and family 11 belongs to endoxylanases with smaller molecular weights (<20 kDa).…”
Section: Introductionmentioning
confidence: 99%